Pengaruh ROE, CR, Ukuran Perusahaan Terhadap Return Saham Pada Perusahaan Manufaktur di BEI - Oktavia, Dila; Wulandari, Putri (Media Akuntansi Perpajakan, 2025)
This study aims to analyze the effect of Return On Equity (ROE), Current Ratio (CR), and Company Size on Stock Return in manufacturing companies in the textile and garment subsector listed on the Indonesia Stock Exchange (IDX) during the period of 2014-2023. The data used are secondary data obtained from the annual financial statements of the companies. The sampling method employed is purposive sampling, resulting in 50 data samples from 5 companies that meet the criteria. Data analysis is conducted using multiple linear regression with the aid of IBM SPSS version 27. The results of the study indicate that partially: first, Return On Equity does not have a significant effect on Stock Return. This indicates that fluctuations in the company's ROE do not directly cause significant changes in the stock returns received by investors during the study period. Second, Current Ratio does not have a significant effect on Stock Return. This finding suggests that the company's ability to meet its short-term obligations does not have a meaningful impact on stock returns. Third, Company Size does not have a significant effect on Stock Return. This implies that the size of the company, measured by total assets, does not significantly influence stock returns. The limitation of this study is its exclusive focus on internal company variables; therefore, it is recommended for future research to consider external variables such as interest rates, inflation, and exchange rates